1993
DOI: 10.1901/jaba.1993.26-99
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effects of Whole‐word and Phonetic‐prompt Error Correction on the Acquisition and Maintenance of Sight Words by Students With Developmental Disabilities

Abstract: We used an alternating treatments design to compare the effects of two procedures for correcting student errors during sight word drills. Each of the 5 participating students with developmental disabilities was provided daily one-to-one instruction on individualized sets of 14 unknown words. Each week's new set of unknown words was divided randomly into two groups of equal size. Student errors during instruction were immediately followed by whole-word error correction (the teacher stated the complete word and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
7
32
0
Order By: Relevance
“…Each 12-to 1 5-mmn session consisted of a next-day test, instruction with ASR and NR error correction, and a same-day test. As described in Barbetta et al (1993), next-day and same-day tests were conducted by the experimenter shuffling the 20 word cards and presenting each individually. No feedback was provided for correct or incorrect responses during next-or same-day tests.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each 12-to 1 5-mmn session consisted of a next-day test, instruction with ASR and NR error correction, and a same-day test. As described in Barbetta et al (1993), next-day and same-day tests were conducted by the experimenter shuffling the 20 word cards and presenting each individually. No feedback was provided for correct or incorrect responses during next-or same-day tests.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study comparing remedial strategies on sight word reading by 5 students with developmental disabilities, we found that wholeword error correction (the teacher stated the complete word and the student repeated it) was more effective than phonetic prompts provided by the teacher (Barbetta, Heward, & Bradley, 1993 (Brigance, 1983) administered prior to the study indicated that Students 1, 2, and 3 read at the preprimer level, Students 4 and 5 read at the first-grade level, and Student 6 read at the second-grade level. One-to-one instruction and testing sessions were conducted 5 days per week in a corner of the special education dassroom.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Error correction for individuals with intellectual disabilities should be direct, immediate, and ensure active student responding. Barbetta, Heward, and Bradley (1993) compared the effects of a direct wordsupply approach to a word-analysis approach in providing error correction during sightword instruction for students with MID. Direct error correction procedures, such as word supply, were more effective than procedures which gradually prompted student responses, such as word-analysis.…”
Section: Error Correctionmentioning
confidence: 99%
“…. Error correction for individuals with intellectual disabilities should be direct (Barbetta, Heward, & Bradley, 1993), immediate (Barbetta, Heward, Bradley, & Miller, 1994;Worsdell, Iwata, Dozier, Johnson, Neidert, & Thomason, 2005), and ensure active student responding (Barbetta, Heron, & Heward, 1993;Worsdell et al, 2005). compared the effects of a direct word-supply approach to a word-analysis approach in providing error correction during sight-word instruction for students with mild intellectual disabilities (MID).…”
Section: However Simultaneous Prompting Does Not Transition To Delaymentioning
confidence: 99%